2014
DOI: 10.1159/000357126
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation of the TNF-α Promoter Region in Peripheral Blood Monocytes and the Cortex of Human Alzheimer's Disease Patients

Abstract: Background: The cytokine tumor necrosis factor-alpha (TNF-α) is elevated in the blood of Alzheimer's disease (AD) patients. Epigenetic DNA modifications of the TNF-α promoter may account for the observed upregulation. Methods: We analyzed blood samples of 50 AD patients and 55 controls plus 4 AD and 4 control cortex samples using bisulfite sequencing PCR. Results: A significant hypomethylation of the TNF-α promoter was found in AD patients' brains but not in their blood. Cortical TNF-α promoter DNA was higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 47 publications
(28 reference statements)
1
17
1
Order By: Relevance
“…Aerobic exercise did not alter the DNA methylation or mRNA expression of either IL6 or TNF. The epigenetic impact of exercise on inflammatory cytokines is relatively unknown, however, several studies have indicated a role for cytokine DNA methylation in inflammatory disease [34][35][36][37]. Although no association between TNF DNA methylation and mRNA expression was detected in the present study, n-3 PUFAs have previously been demonstrated to reverse the epigenetic changes observed with inflammation in skeletal muscle cells.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Aerobic exercise did not alter the DNA methylation or mRNA expression of either IL6 or TNF. The epigenetic impact of exercise on inflammatory cytokines is relatively unknown, however, several studies have indicated a role for cytokine DNA methylation in inflammatory disease [34][35][36][37]. Although no association between TNF DNA methylation and mRNA expression was detected in the present study, n-3 PUFAs have previously been demonstrated to reverse the epigenetic changes observed with inflammation in skeletal muscle cells.…”
Section: Discussioncontrasting
confidence: 80%
“…Increases in markers of oxidative stress and circulating levels of inflammatory cytokines, such as IL-6 and TNFa, have been shown to alter the expression of DNA methyltransferases (DNMTs) [28][29][30][31][32] and influence DNA methylation patterns [11,33]. DNA methylation of inflammatory cytokines have been associated with various inflammatory diseases including IL6 with Rheumatoid Arthritis [34] and obesity [35]; TNF DNA methylation with type 2 diabetes [36] and Alzheimer's disease [37]. Despite increased circulating levels of inflammatory cytokines post-exercise [14,23], the impact of exercise on the DNA methylation of genes encoding inflammatory cytokines such as IL6 and TNF remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, hypomethylation of the TNF-α promoter was revealed in the AD brain cortex, while unchanged methylation values in cases versus controls were detected in blood [28]. Similarly, increased methylation of the APP promoter was specifically detected in the AD temporal cortex [20], whereas no difference was found in the parietal or frontal cortex and the cerebellum [16,20].…”
Section: Discussionmentioning
confidence: 97%
“…Two major epigenetic mechanisms are the post‐translational modification of histone proteins in chromatin and the methylation of DNA itself . Several studies have shown the potential association of TNF‐α promoter methylation with selective neuronal vulnerability , weight loss , age , central adiposity and Alzheimer's disease . Recently, it has been reported that white individuals with chronic periodontitis (CP) show hypermethylated status at two cytosine–guanine dinucleotide (CpG) sites in the TNF‐α promoter and decreased levels of TNF‐α transcriptional expression in the gingival tissues .…”
mentioning
confidence: 99%